2020
DOI: 10.1523/jneurosci.0767-20.2020
|View full text |Cite|
|
Sign up to set email alerts
|

Hippocampal Theta Oscillations Support Successful Associative Memory Formation

Abstract: Models of memory formation posit that recollection as compared to familiarity-based memory depends critically on the hippocampus, which binds features of an event to its context. For this reason, the contrast between study items that are later recollected versus those that are recognized on the basis of familiarity should reveal electrophysiological patterns in the hippocampus selectively involved in associative memory encoding. Extensive data from studies in rodents support a model in which theta oscillations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 51 publications
7
34
0
Order By: Relevance
“…The data reported so far indicate that across trials, memory-relevant behavioral responses fall onto a consistent phase of a theta oscillation. The presence of such an oscillation, determined on the basis of one response per trial, implies phase consistency across trials in the neural oscillations in hippocampus presumed to underly memory formation and reinstatement, as previously shown by Kota et al 44 , and Fell et al 45 . We hypothesized that this phase consistency, induced by events in the trial, persists until the participant successfully encodes or retrieves the memory (expected to slightly precede the button press).…”
Section: Resultsmentioning
confidence: 54%
“…The data reported so far indicate that across trials, memory-relevant behavioral responses fall onto a consistent phase of a theta oscillation. The presence of such an oscillation, determined on the basis of one response per trial, implies phase consistency across trials in the neural oscillations in hippocampus presumed to underly memory formation and reinstatement, as previously shown by Kota et al 44 , and Fell et al 45 . We hypothesized that this phase consistency, induced by events in the trial, persists until the participant successfully encodes or retrieves the memory (expected to slightly precede the button press).…”
Section: Resultsmentioning
confidence: 54%
“…In rodents, it has been shown that social stimuli elicit high theta, and fearful stimuli elicit low theta (Tendler and Wagner, 2015 ), and type 2 theta oscillations have been shown to be associated with increased risk-taking behavior (Mikulovic et al, 2018 ). In humans, theta frequencies are lower overall (Jacobs, 2014 ), but it is still possible to distinguish high and low theta frequencies, with low theta supporting encoding and retrieval of memories (Kota et al, 2020 ). Clearly, what the particular theta frequency is has functional significance, and so how theta frequencies are controlled is functionally important to consider.…”
Section: Introductionmentioning
confidence: 99%
“…Our model can account for data from both rodents and humans, which connects human episodic memory behaviour to synaptic modifications induced by non-neurophysiological stimulation in the animal brain. Our model provides an explanation to the findings in human electrophysiological studies, which show that hippocampal theta synchronization supports episodic encoding, especially when there is need to form arbitrary associations (Backus et al, 2016;Kota et al, 2020;Staudigl & Hanslmayr, 2013). Though those findings are correlational rather than causal, our model suggests that theta synchronization links to stronger synaptic weights between corresponding hippocampal neurons after encoding.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, hippocampal theta phase resetting has been found to occur after stimulus onset during memory encoding (Rutishauser et al, 2010). Further, Kota et al (2020) shows in an iEEG study that ongoing hippocampal theta oscillation phase was reset to support episodic encoding. Such phase reset indicates a mechanism for inputs to be more likely to undergo LTP (McCartney et al, 2004;Mormann et al, 2005;Rizzuto et al, 2003).…”
Section: Discussionmentioning
confidence: 94%